Great ape health watch: Enhancing surveillance for emerging infectious diseases in great apes. Issue 4 (7th April 2022) - Zimmerman, Dawn M.; Mitchell, Stephanie L.; Wolf, Tiffany M.; Deere, Jessica R.; Noheri, Jean Bosco; Takahashi, Emi; Cranfield, Michael R.; Travis, Dominic A.; Hassell, James M.
Abstract: Infectious diseases have the potential to extirpate populations of great apes. As the interface between humans and great apes expands, zoonoses pose an increasingly severe threat to already endangered great ape populations. Despite recognition of the threat posed by human pathogens to great apes, health monitoring is only conducted for a small fraction of the world's wild great apes (and mostly those that are habituated) meaning that outbreaks of disease often go unrecognized and therefore unmitigated. This lack of surveillance (even in sites where capacity to conduct surveillance is present) is the most significant limiting factor in our ability to quickly detect and respond to emerging infectious diseases in great apes when they first appear. Accordingly, we must create a surveillance system that links disease outbreaks in humans and great apes in time and space, and enables veterinarians, clinicians, conservation managers, national decision makers, and the global health community to respond quickly to these events. Here, we review existing great ape health surveillance programs in African range habitats to identify successes, gaps, and challenges. We use these findings to argue that standardization of surveillance across sites and geographic scales, that monitors primate health in real‐time and generates early warnings of disease outbreaks, is an efficient, low‐cost step to conserve great ape populations. Such a surveillance program, which we call "Great Ape Health Watch" would lead to long‐term improvements in outbreak preparedness, prevention, detection, and response, while generating valuable data for epidemiological research and sustainable conservation planning. Standardized monitoring of great apes would also make it easier to integrate with human surveillance activities. This approach would empower local stakeholders to link wildlife and human health, allowing for near real‐time, bidirectional surveillance at the great ape‐human interface. Abstract : End‐to‐end flows of great ape data within the Great Ape Health Watch system, depicting the potential interface with other existing health surveillance systems and portable diagnostic platforms. Highlights: This study reviewed existing great ape health surveillance programs in Africa and Asia to identify successes and challenges, and highlight the need for a standardized approach to great ape health surveillance. We propose "Great Ape Health Watch"—an integrated, real‐time monitoring system for great ape and human health that would generate early warnings of disease outbreaks, as a cost‐efficient strategy to secure future great ape conservation. Integrated ape–human syndromic surveillance would not only provide continuity in outbreak preparedness and data collection, but also empower local stakeholders to link wildlife and human health for impactful conservation and healthcare provisions.